Preoperative Facial Muscle Imaging Predicts Final Facial Function after Facial Nerve Grafting - Kaylie, David M.; Wax, Mark K.; Weissman, Jane L. (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Our goal was to determine whether preoperative MR imaging of facial muscles predicts facial function after facial nerve grafting.METHODS: A retrospective review of all patients undergoing facial nerve grafting between 1997 and 2001 revealed 26 patients. Twelve of the patients had adequate preoperative MR images available for review and had undergone clinical follow-up for at least 12 months. Eight had malignant parotid tumors, and four had benign skull base or parotid tumors. Preoperative facial muscle MR imaging appearance was categorized as symmetrical or asymmetrical. The asymmetrical images were further classified into mild or pronounced asymmetry. Preoperative facial function was classified by using the House-Brackmann scale. Postoperative function was graded with the May scale.RESULTS: Four patients had symmetrical facial muscles shown by preoperative MR imaging, three had mild asymmetry, and five had pronounced asymmetry. No or mild asymmetry had an 86% positive predictive value for good to excellent functional outcome. Eighty percent of patients with pronounced asymmetry experienced poor functional outcomes. Six of eight patients with malignant and perineural tumors at surgery had asymmetrical facial muscles revealed by preoperative MR imaging studies.CONCLUSION: Symmetrical or mildly asymmetrical facial muscles are predictive of good facial function after nerve grafting. Pronounced asymmetry of facial muscles on MR images is predictive of poor facial function after grafting. Asymmetric facial muscles on preoperative MR images are associated with perineural tumor spread in patients with malignant disease.